PROMOTING EFL LISTENING AND SPEAKING SKILLS THROUGH PODCAST: TEACHERS’ BELIEFS AND PRACTICES - Harahap, Muhammad Qudsi Amirullah; Rizal, Daviq (Universitas Islam Sumatera Utara (UISU), 2023)
The purpose of this study was to investigate a method for integrating English learners' podcasting skill development by teacher beliefs. This research design used an online form basis which contains multiple choices and also open ended questions. Participants involved in this study were 17 participants. The procedure used in this study was the use of forms and there was also an interview session. Data analysis which was known in this study was that 82,4% respondents were familiar with podcast media for learning English. In this research, a qualitative descriptive research method was employed, revealing the efficacy of podcasts as a valuable medium for English language learning, particularly in the domains of listening and speaking skills. Utilizing podcasts to foster English as a Foreign Language (EFL) speaking and listening proficiency emerged as an engaging and fruitful technique, demonstrating its potential as an effective tool for language enhancement. Consequently, the study advocates for the incorporation of podcasts into the EFL curriculum.